Indian Politics: Haunted by Spectre of Post-democracy?. (December 2017) - Verma, Ravindra Kumar
The dawn of 21st century has witnessed some new features of democratic politics that seem to be shifting away from what we call democratic. The impact of globalisation has created such a nexus among elites of politics–corporates–media that has made political regimes to ignore the democratic norms and well-being of common masses and overemphasise economic growth and corporate-friendly policy priorities. Besides, the approach of the political actors (parties and politicians), in the process of power-seeking, has shown unconventional trends. These features do not resemble either dictatorship or totalitarianism; rather they depict trends of aristocratic mode of decision-making by using democratic framework and institutions. Such trends have been termed as 'post-democracy' by recent Western scholarship. Indian politics is not an exception. These trends have created an imbalance between interest of social classes and corporative interests which has prompted political regimes to take tough decisions, in despotic ways. Though the present article does not posit that Indian democracy is on the brink, it attempts to underline the post-democratic features visible in Indian politics through examination of (a) party politics in terms of democratic framework, ideology, policy initiations and reforms, electioneering, etc.; (b) politicians–corporates–media nexus; and (c) modes and trends of politicians in communicating and relating with the electorate.